2016
DOI: 10.1371/journal.pone.0146511
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Glucose Sensation Can Increase the Fitness of Saccharomyces cerevisiae Lacking Mitochondrial DNA

Abstract: Damage to the mitochondrial genome (mtDNA) can lead to diseases for which there are no clearly effective treatments. Since mitochondrial function and biogenesis are controlled by the nutrient environment of the cell, it is possible that perturbation of conserved, nutrient-sensing pathways may successfully treat mitochondrial disease. We found that restricting glucose or otherwise reducing the activity of the protein kinase A (PKA) pathway can lead to improved proliferation of Saccharomyces cerevisiae cells lac… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 136 publications
1
9
0
Order By: Relevance
“…This may be at least partially explained by its effect on the stability of the cytosolic proteome in addition to its role in processing unimported mitochondrial proteins. Similarly, the Dunn group found that a dot6Δ tod6Δ double mutant is q o -lethal [44]. DOT6 and TOD6 are transcriptional repressors of genes required for ribosomal biogenesis and protein synthesis in the TOR-signaling pathway.…”
Section: Conditions That Can Induce Mposmentioning
confidence: 94%
“…This may be at least partially explained by its effect on the stability of the cytosolic proteome in addition to its role in processing unimported mitochondrial proteins. Similarly, the Dunn group found that a dot6Δ tod6Δ double mutant is q o -lethal [44]. DOT6 and TOD6 are transcriptional repressors of genes required for ribosomal biogenesis and protein synthesis in the TOR-signaling pathway.…”
Section: Conditions That Can Induce Mposmentioning
confidence: 94%
“…However, loss of mtDNA has also been shown to cause a reduction in ISC formation due to loss of membrane potential and impaired import of ISC biosynthesis enzymes. Hence, loss of mtDNA also activates the iron signaling cascade . Importantly, such conditions should affect not only ISC biosynthesis but also heme formation and hence it is interesting to note that each have their own unique signaling pathway (see below).…”
Section: Signaling From Within Mitochondria To the Nucleusmentioning
confidence: 99%
“…It is therefore not surprising that mitochondrial function is coupled to signaling responses controlling arginine biosynthesis. It was recently shown that genes involved in the synthesis of arginine were highly induced upon mtDNA loss . Moreover, a significant reduction in the expression of two genes involved in aromatic amino acid catabolism, ARO9 and ARO10 , occurred as a result of the loss of mtDNA.…”
Section: Signaling From Within Mitochondria To the Nucleusmentioning
confidence: 99%
See 2 more Smart Citations